1969
DOI: 10.1139/v69-290
|View full text |Cite
|
Sign up to set email alerts
|

Associative-detachment reactions of O and O2 by O2(1Δg)

Abstract: The flowing afterglow technique has been used to study the electron detachment reactions OZ(lAg) + 02--f 2 0 2 + e and 02('Ag) + 0--f O3 + e The rates of these reactions are sufficiently fast to make them important processes in D region ionospheric chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2

Year Published

1975
1975
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 1 publication
2
44
2
Order By: Relevance
“…These cross-sections are roughly an order-ofmagnitude larger than the corresponding geometrical cross section, R C 2 , which are also shown in the figure. The crosssections for Na 7 Ϫ are smaller than for Na 19 Ϫ . Therefore, the fact that two partial waves (lϭ0,2) are dominant in the first case, while only one (lϭ1) is dominant in the second case does not have a significant influence.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…These cross-sections are roughly an order-ofmagnitude larger than the corresponding geometrical cross section, R C 2 , which are also shown in the figure. The crosssections for Na 7 Ϫ are smaller than for Na 19 Ϫ . Therefore, the fact that two partial waves (lϭ0,2) are dominant in the first case, while only one (lϭ1) is dominant in the second case does not have a significant influence.…”
Section: Resultsmentioning
confidence: 81%
“…5 and will be shown below, due to the long-range nature of the Penning detachment process, the dipole-dipole term of the multipolar expansion of 1/r 12 is responsible for most of the relevant couplings of the process. Since the ejected electrons initially occupy the 1p and 2s orbitals for Na 7 Ϫ and Na 19 Ϫ , respectively, electrons will be mostly ejected into continuum orbitals with lϭ0 and 2 ͑Na 7 Ϫ ), and lϭ1 (Na 19 Ϫ ). Higher angular momenta lead to a redistribution of the final state population but barely affect the value of the total crosssection ͑see Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(See Phelps, 1969. ) However, k 2 is described as uncertain within a range of (+900%, -90%) (Fehsenfeld et al, 1969). We found that we could improve the agreement between the computed and measured peak n e by increasing the assumed value of k 2 from 2 x 10~1 0 cm 3 /s to 1 x 10~9.…”
Section: Computations and Comparisons With The Datamentioning
confidence: 80%
“…The first reported instance of detachment of an electron from a negative ion by collision with an excited species 7 was not really Penning detachment, although closely related to it. This was the observation of associative detachment of electrons from O − and O 2 − by collision with excited oxygen molecules, O 2 ( 1 Δ g ) to form ozone, O 3 .…”
Section: Penning Detachmentmentioning
confidence: 99%